The arbitrary word: a study of Fenêtres dormantes et Porte sur le toit by René Char - Alselmi, André Luiz (Lettres Françaises, 2015)
René Char left a vast poetic production which is little studied (especially in Brazil ), because his work is considered difficult to understand and, therefore, is said to be hermetic. However, the interest of thecritics has increased and, little by little, has gained the deserved space, crossing its territorial and linguistic boundaries, making itself known to the honourable spirits for their efforts in deciphering poetic messages. The criticism concerning the work of Char often tries to understand his poetry from his biography, or else, seeks to reflect on the philosophical grounds that permeate his poetry. Adopting another type of analysis, this article presents a study of Fenêtres dormantes et porte sur le toit – book that brings together texts written between 1973 and 1979 – focusing on the stylistic and formal issues, as well as on the surrealist heritage we find in his poems. Therefore, based on the concepts that guide the modern lyricism, this paper focuses on aspects of the work of the poet that lie in the specific field of poetry: poetic form, figurative language and rhetoric.